(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Evaluation of the synergy effect between bio-fertilizer and irradiated oligochitosan was conducted to determine the growth and yield of the test plants. Study for synergistic effect of biofertilizer and irradiated oligochitosan, some positive effect such as plant growth promoter and pathogen suppression in tomato yield in the green house pot experiment. It was guessed that oligocitosan induced resistance for seedling treated. Data showed synergistic effect using disease control intensities, In this case, synergistic effect between biofertilizer and oligochitosan is clearly positive. Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 80-85